Development of Hots-based LKPD on Material Changes in the Form of Objects for Class IV Elementary School Students - Siregar, Hasny Delaila; Zunidar, Zunidar (FKIP - Universitas Riau, 2025)
This study aims to determine the validity, practicality, and effectiveness of HOTS-based LKPD on the material of Changes in Object Forms for grade IV elementary school students. The development model used is the 4D model (Define, Design, Develop, Disseminate). Data were collected through interviews, validation sheets, teacher and student response questionnaires, and higher-order thinking tests (Pretest and posttest). The validation results showed a score of 91% from the material expert and 89.5% from the media expert, which is included in the very valid category. Regarding practicality, the teacher response questionnaire score was 94.2% and the students' 90%, indicating that the LKPD is efficient. The effectiveness of the LKPD is seen from the N-Gain result of 0.64, which is in the medium category. Thus, this HOTS-based LKPD is considered valid, practical, and effective enough to be used in learning science on the material of changes in the form of objects.